ANALISIS USAHATANI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNTUNGAN USAHATANI CABAI MERAH DI KECAMATAN TULANG BAWANG TENGAH KABUPATEN TULANG BAWANG BARAT - Afaf Faadhilah Risyanti; Bustanul Arifin; Lina Marlina (Lampung University, 2021)
This study aims to analyze farming and factors that affecting the profit of red chilli farming in Tulang Bawang Tengah Sub-District, Tulang Bawang Barat Regency. This research uses survey method. The research is located in Tulang Bawang Tengah Sub-Distric, Tulang Bawang Barat Regency, which was conducted in April-May 2019. The number of respondent are 57 farmers taken by random sampling method. Data are analyzed using quantitative and qualitative analysis. Furthermore, farming analysis is analyzed using income analysis and by counting the value of R/C to cash cost and total cost. Factors affecting profit function are analyzed by profit analysis UOP (Unit Output Price), which is a derived of the cobb douglas production function and normalized by output price. The results show that the average income of red chilli farming in Tulang Bawang Tengah Sub-District base on cash costs and the total cost is Rp47,486,701.79/hectare and Rp22,229,238.35/hectare, respectively. Red Chilli farming give a profit as the value of R/C to cast costs and total cost are 1,99 and 1,33. Factors of land area, seed price, SP36 fertilizer price, manure price, NPK fertilizer price, insecticide price, fungicide price and labor wages significantly affect to the profits of red chilli farming in Tulang Bawang Tengah Subdistric.Keywords : income, profit, and red chilli